Adoption of Islamic Rural Banks in Indonesia: The Role of Brand Personality and Religiosity - Purwanto Purwanto; Ali Ibrahim Dasuki; Mutia Pamikatsih (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Islamic Rural Banks (henceforth BPRS) represent a rapidly expanding segment of the Islamic banking industry in Indonesia, marked by increasing adoption of their financial products. While customer religiosity is often assumed to be a key determinant of Islamic banking adoption, its influence is not always direct and may operate through more complex mechanisms, such as banks’ brand personality. Accordingly, this study examines the mediating role of Islamic banks’ brand personality in the relationship between customer religiosity and the adoption of BPRS products. Using a quantitative approach, survey data were collected from 400 BPRS customers across seven provinces in Indonesia. Respondents were selected using a non-probability sampling technique, with the sample size determined by the Slovin formula to ensure representativeness at a 5% margin of error. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that brand personality has a positive and significant effect on the adoption of BPRS products, whereas religiosity does not exert a significant direct influence. Importantly, brand personality is found to mediate the relationship between religiosity and product adoption. These findings suggest that developing a strong and distinctive brand personality is strategically crucial for Islamic rural banks, enabling them to translate customers’ inherent religiosity into actual service adoption beyond purely ideological appeals.